Flexural strength acrylic resin heat cured for denture base in soaking mouthwash containing siwak - Didik Marsigid; Mujiwati Mujiwati; Sophia Nursabila Pebriani (Jurnal Medali, 2023)
Background: Teeth have an important role in a person, the most common cause of tooth loss is caries and periodontal disease. Tooth loss can be overcome by making dentures, removable denture components consist of dental elements, clasps, and bases. The denture base is part of denture that rests on soft tissues of oral cavity and is where denture elements are attached. One of the important mechanical properties for denture bases is flexural strength. Acrylic resin denture base material has disadvantage that it absorbs liquid and is porous so that food debris can settle and become a place for microorganisms to grow and multiply. This study aims to determine flexural strength of heat cured acrylic resin for denture base in immersing mouthwash containing siwakMethod: this laboratory experiment used 12 linear specimens with a size (64 x 10 x 3.3 mm) ± 0.2 mm in accordance with ISO 20795-1:2013 which were divided into 2 groups, the first group was immersed in aquabidest (control), the second group was immersed in mouthwash containing siwak for 7 days. The data obtained were then tested using the Independent T-testResult: There was no significant difference (p > 0.05) in the flexural strength of heat cured acrylic resinConclusion: From the research, there is no effect flexural strength of heat cured acrylic resin in soaking mouthwash containing siwak. The effect of mouthwash containing siwak on the flexural strength of heat-cured acrylic resin was not significant.